2020
DOI: 10.1042/bcj20200029
|View full text |Cite
|
Sign up to set email alerts
|

Processing of the SARS-CoV pp1a/ab nsp7–10 region

Abstract: Severe acute respiratory syndrome coronavirus is the causative agent of a respiratory disease with a high case fatality rate. During the formation of the coronaviral replication/ transcription complex, essential steps include processing of the conserved polyprotein nsp7-10 region by the main protease M pro and subsequent complex formation of the released nsp's. Here, we analyzed processing of the coronavirus nsp7-10 region using native mass spectrometry showing consumption of substrate, rise and fall of interm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
119
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 41 publications
23
119
0
1
Order By: Relevance
“…One would expect that these nsp's are cleaved in an order that reflects their associations with one another and other key proteins in line with the viral needs during the production of new viruses. Nsp10 and nsp9 have no reported structures involving either nsp7 or nsp8 ( Figure 1) this was also confirmed by by Krichel and coauthors [6] therefore it is not surprising that it is released from the polyprotein first as it requires no other partners to carry out its function. A spherical dodecameric structure has been reported that is composed of trimeric units of nsp10 alone [11] and a monomeric structure of nsp10 has also been reported [12].…”
Section: The Order In Which Nsp's Are Released Links To Different Funsupporting
confidence: 68%
See 3 more Smart Citations
“…One would expect that these nsp's are cleaved in an order that reflects their associations with one another and other key proteins in line with the viral needs during the production of new viruses. Nsp10 and nsp9 have no reported structures involving either nsp7 or nsp8 ( Figure 1) this was also confirmed by by Krichel and coauthors [6] therefore it is not surprising that it is released from the polyprotein first as it requires no other partners to carry out its function. A spherical dodecameric structure has been reported that is composed of trimeric units of nsp10 alone [11] and a monomeric structure of nsp10 has also been reported [12].…”
Section: The Order In Which Nsp's Are Released Links To Different Funsupporting
confidence: 68%
“…Similarly, nsp9 has been shown to form dimeric structures that bind RNA [13,14] (Figure 1). Krichel and coauthors also confirmed the presence of nsp9 monomers and dimers in solution but no complexes of nsp9 with the other nsp's [6]. Therefore, it seems logical that nsp9 will be cleaved next rather than nsp7.…”
Section: The Order In Which Nsp's Are Released Links To Different Funmentioning
confidence: 92%
See 2 more Smart Citations
“…Of these proteins, (1) nsp1 suppresses the antiviral host response, (2) nsp3 is a papain-like protease, (3) nsp5 is a 3CLpro (3C-like protease domain), (4) nsp7 makes a complex with nsp8 to form a primase, (5) nsp9 is responsible for RNA/DNA binding activity, (6) nsp12 is an RNA-dependent RNA polymerase (RdRp), (7) nsp13 is confirmed as a helicase, (8) nsp14 is a 3′-5′ exonuclease (ExoN), 9) nsp15 is a poly(U)-specific endoribonuclease (XendoU). The remaining nsps are involved in transcription and replication of the viral genome [13,46,47].…”
Section: Sars-cov-2 Genome Organizationmentioning
confidence: 99%